Nodular presentation of Dirofilaria repens infection in a cat mimicking a fibrosarcoma. (9th December 2016) - Manzocchi, Simone; Lendner, Matthias; Piseddu, Eleonora; Sebastiani, Valeria; Morabito, Simona; Daugschies, Arwid; Pantchev, Nikola
Abstract: A cat with multiple subcutaneous nodules suggesting a soft tissue sarcoma by physical and computed tomographic examination was diagnosed as being affected by subcutaneous filariosis based on cytologic and ultrasonographic assessments. Nodules were surgically removed and extracted nematodes were identified by PCR as Dirofilaria repens . Furthermore, DNA of Dipetalonema dracunculoides (syn. Acantocheilonema dracunculoides ) was detected by PCR, with no evidence of circulating microfilariae. To the best of the authors' knowledge, this represents the first report describing adults of D repens in multiple subcutaneous nodules in a cat. Cytopathologic examination allowed characterization of the parasitic nature of the nodules. Veterinary practitioners should be aware of the possible nodular presentation of D repens in cats and should include D repens in the differential diagnosis of subcutaneous neoformations in the cat.